Determination the Optimum Conditions of the Activity and Stability of Lipase Extracted from Sunflower Germinated Seeds - Al-Haidari, Alaa M. Dh.; Alsaadawi, Ibrahim S.; Khudhair, Saad Hussein (Iraqi Journal of Science, 2021)
The present study was conducted to determine the optimum conditions required for lipase enzyme activity extracted from germinated sunflower seeds, including temperature, pH, agitation, time of incubation, enzyme concentration, substrate type, and concentrations of mineral salts and EDTA. Optimum pH, temperature and time of incubation required for lipase stability were also determined. The results showede optimum lipase activity (3.251U/ml) wasund at 30 ÌŠC and pH 7 after 20 minutes of incubation when using 1 ml lipase enzyme with 0.02 ml of CaCl2 (10 mM) at 100 rpm of agitation and in the presence of olive oil as the substrate for enzyme reaction. EDTA appeared to have inhibitory effects, while Ca+2 and Mg+2 have stimulatory effects on lipase activity. The values of lipase activity, total activity, and specific activity measured under optimum conditions were increased by 36.99%, 36.95%, and 38.21% over control, respectively. The enzyme showed stability at a temperature ranged between 30 to 50 ËšC, pH between 7 to 8, and time of incubation between 10 to 40 minutes. These results suggest that lipase enzyme extracted from germinated sunflower seeds have stability that depends on pH, temperature, and incubation period, which enables it to be used in different industries.